2020
DOI: 10.48550/arxiv.2011.07093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interdicting Restructuring Networks with Applications in Illicit Trafficking

Abstract: We consider a new class of max flow network interdiction problems, where the defender is able to introduce new arcs to the network after the attacker has made their interdiction decisions. We provide an example of when interdiction can result in an increase to the maximum flow, and prove properties of when this restructuring will not increase the value of the minimum cut, which has important practical interpretations for problems of disrupting drug or human trafficking networks. In particular, it demonstrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…This paradox aligns with the theoretical analysis in Kosmas et al (Kosmas et al 2020), where they observed that current law enforcement policy typically recommended interdicting participants in drug smuggling networks that would trigger restructuring arcs that would cross the minimum cut. We find that a similar situation occurs for our conceptualizations of sex trafficking networks, thus indicating that both disrupting current operations and their ability to restructure (especially recruit) is critial.…”
Section: Responsible Use Case Study: Network Interdictionsupporting
confidence: 80%
See 3 more Smart Citations
“…This paradox aligns with the theoretical analysis in Kosmas et al (Kosmas et al 2020), where they observed that current law enforcement policy typically recommended interdicting participants in drug smuggling networks that would trigger restructuring arcs that would cross the minimum cut. We find that a similar situation occurs for our conceptualizations of sex trafficking networks, thus indicating that both disrupting current operations and their ability to restructure (especially recruit) is critial.…”
Section: Responsible Use Case Study: Network Interdictionsupporting
confidence: 80%
“…The other player, the defender, then operates the network as per the max flow problem. Max flow network interdiction has successfully been applied to disrupting illicit drug trafficking networks (Baycik et al 2018, Malaviya et al 2012, Shen et al 2021, Kosmas et al 2020, and has been identified as an analytical tool to help address sex trafficking (Smith & Song 2020). Some max flow network interdiction models have been proposed for disrupting human trafficking (Mayorga et al 2019, Tezcan & Maass 2020.…”
Section: Responsible Use Case Study: Network Interdictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research related to OR and analytics efforts to reduce homelessness and the supply of sex and labor trafficking victims has only recently received attention and largely focus on three broad areas: the scope of the problem (Kosmas et al, 2020;Brelsford and Parakh, 2018), frameworks for addressing the crisis (Taylor, 2018;Kővári and Pruyt, 2014), and appropriate allocation of scarce resources to combat HT and homelessness (Chan et al, 2018;Petry et al, 2021). A second body of OR literature focuses on detection of hidden HT victims (Keskin et al, 2021;Kapoor et al, 2017;Mensikova and Mattmann, 2017), movement patterns of covert traffickers (McDonald et al, 2021;Yao et al, 2021;Amin, 2010) and long-term intervention approaches to prevent trafficking or retrafficking by increasing the efficiency and effectiveness of public services (Amadasun, 2020), as well as improving access to supportive and rehabilitative services (Azizi et al, 2018).…”
Section: Or Human Trafficking and Homelessnessmentioning
confidence: 99%